Dexmedetomidine induced catecholamine suppression in pheochromocytoma - Singh, Sanjeev (Medknow Publications & Media Pvt Ltd, 2014)
Pheochromocytoma is a neuroendocrine tumour of chromaffin cells, though rare but a known cause of paroxysmal hypertension with a triad of headache, diaphoresis and palpitation. The biochemical diagnosis of pheochromocytoma is based on estimation of plasma nor-adrenaline, adrenaline and their metabolites in plasma or urine. Clonidine suppression test is performed to differentiate the raised catecholamine level due to pheochromocytoma or other than heochromocytoma especially in cases where plasma nor-adrenaline levels are less than 2000 pg/ml. Clonidine is stated to be unable to suppress catecholamine level in cases of pheochromocytoma, therefore we tested the other α(2)-agonist Dexmedetomidine intravenous in a case of Pheochromocytoma with remarkably raised nor- adrenaline (25,183 pg/ml) and found 49.42% suppression.